Analysis of Repairable k-out-of-n System Model Using Inter-Arrival Failure Times - Gurcan, Mehmet; Gural, Yunus; Gokdere, Gokhan (E D P Sciences, 2018)
Examination of repairable k-out-of-n system which has an important place in systems is an important application area of reliability theory. In general, the reliability analysis of a repairable system is based on the distribution of the lifetimes of the components in the system. In this paper, the reliability analysis of the repairable k-out-of-n system is made through the inter-arrival failure times of the components in the system.
3rd International Conference on Computational Mathematics and Engineering Sciences (CMES) -- MAY 04-06, 2018 -- Final Int Univ, Girne, CYPRUS
Keywords: Markov Renewal Processes